Pelindungan Konstitusional Masyarakat Hukum Adat dalam Tata Kelola Energi Nasional - Wijaya, Karisma Anggraeni; Qurbani, Indah Dwi; Arrsa, Ria Casmi (RechtJiva, 2026)
National energy development constitutes a strategic instrument of the state to achieve energy security and sustainable development. However, in practice, energy projects are often developed in areas that socially and historically constitute the living space of indigenous peoples. This situation becomes problematic when energy governance has not yet provided adequate mechanisms for protecting the rights of indigenous peoples. The absence of such protection mechanisms has the potential to trigger social conflicts, ecological degradation, and violations of the constitutional rights of indigenous peoples. This article aims to analyze the absence of protection mechanisms for indigenous peoples within national energy governance and its constitutional implications from the perspective of economic constitution. This research employs a normative legal research method using statutory, conceptual, and constitutional approaches. Legal materials were collected through library research consisting of primary, secondary, and tertiary legal sources, and were analyzed qualitatively using a descriptive-analytical method and deductive reasoning to identify normative gaps within the existing regulatory framework. The results show that national energy governance has not explicitly accommodated the recognition of customary land rights, meaningful participation, and the implementation of the Free, Prior and Informed Consent (FPIC) principle for indigenous peoples. This normative gap is inconsistent with constitutional principles that recognize and respect the existence of indigenous peoples and mandate that the management of natural resources be directed toward the greatest prosperity of the people. Therefore, strengthening rights-based energy governance is necessary through the integration of explicit protection mechanisms for indigenous peoples within the national energy legal framework.